RT-CaCC towards a cache-aware congestion control mechanism in wireless sensor networks - Alipio, Melchizedek I.; Tiglao, Nestor Michael C. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Reliability of data transport in Wireless Sensor Networks is critical in the presence of high packet loss level in the network. Data caching and congestion control mechanisms can enhance the reliability performance of transport protocols during congestion. However, these two mechanisms are designed independently for most cache-based transport protocols leading to underutilization of intermediate caching. This work proposed new techniques that lead to the improvement of cache-based transport protocols in terms of cache utilization. First, a classification of cache management policies derived from state-of-the-art cache-based transport protocols was developed. Second, the performance of intermediate caching at packet loss scenarios was analyzed in terms of transmission window size. Third, a dynamic cache-aware rate control mechanism that utilizes the optimal transmission window range in terms of cache size was developed. Finally, a transport protocol with a cache-aware congestion control mechanism called RT-CaCC was developed. RT-CaCC utilizes cache management policies such as cache insertion, cache elimination, and cache size allocation to mitigate packet losses in the network while improving cache memory usage. Results showed that the RTCaCC obtained significant improvement gain compared with baseline protocols. In addition, RT-CaCC consistently outperformed other cache-based transport protocols like DTC and ERCTP in terms of resource utilization.
Thesis (Doctor of Philosophy in Electrical and Electronics Engineering)--University of the Philippines Diliman
Keywords: Wireless sensor networks; Computer network protocols; Cache memory; Intermediate caching